LABOR AND EMPLOYMENT LAW AND PREVENTIVE STRATEGIES SMOKE-RINGS IN THE WORKPLACE - WILLIAMS,JR (Tufts Archival Research Center, 2007)
Labor and Employment Law and Prevention Strategies newsletter excerpt of speech on smoke-rings in the workplace. Offers background on workplace smoking legislation. Discusses methods of regulation, ranging from state legislation to city, county, and town ordinances. Finds that constitutioonal rights do not guaruntee a smoke-free environment but that litigation brought by adversely affected non smokers has been successful. Talks about employees' remedies and employers' potential exposure, compliance with regulations, and avoiding potential liability.